Narrative of the voyage of H.M.S. Herald during the years 1845-51, under the command of Captain Henry Kellett, R.N., C.B. [electronic resource] : being a circumnavigation of the globe, and three cruizes to the Arctic regions in search of Sir John Franklin - Seemann, Berthold, 1825-1871. (London : Reeve and Co., 1853)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 40364-40366. "In two volumes. Vol. I." Electronic reproduction. Mode of access: Internet. 44